(untitled) (Research, Society and Development, 2021)
It is estimated that seven million human lives are lost worldwide due to exposure to air pollutants from fixed and mobile sources, in urban or rural areas. In this context, the World Health Organization warns about the economic viability of applying sustainable public policies to mitigate the effects of population exposure to atmospheric contaminants, proving a return on investment linked to the reduction of health costs for the population. However, due to the diversity of variables involved in the problem and the divergence between them for each region studied, understanding the scenarios in which these projects will be carried out is essential. This research aims to identify the association between exposure to fine and coarse particulate matter with deaths from cardiovascular diseases in the Brazilian municipality of Taubaté / SP through the analysis of the association between deaths from cardiovascular diseases and the variation in PM2,5 and PM10, as well as social and financial costs of premature deaths inherent to the studied context. The preliminary results confirm the hypothesis raised, presenting a loss of €17.506.500,00 for the period between 2016 and 2018.